Internet systems in BEN RAS - new services for users - S. A. Vlasova (Библиосфера, 2014)
The subject of the article is automated systems worked out by the Library for Natural Sciences (LNS) specialists: the expert system of acquisition, the publications` ordering system supported by RFBR, virtual exhibitions. In all these systems, the user is provided with the access to bibliographic descriptions and electronic samples of editions` pages from LNS funds.